Financial Evaluation to Select the Best Water Hyacinth Harvester to Improve Water Resources in Thailand - Saneewong Na Ayuttaya, Suwimon (Agriculture and Natural Resources, 2015)
Cost analysis for the eradication of water hyacinth was undertaken using a mechanical water hyacinth harvester. Two foreign harvester models (V 4702 and S 2800) were ordered and a prototype water hyacinth harvester was designed and built in Thailand. Based on reports, there are 4.52 million t of water hyacinth in Thailand. A budget of USD 0.27 million per year would eradicate 477,000 t using water hyacinth harvesters. The operating cost is not satisfactory and the permanent eradication of water hyacinths would involve an operating cost of USD 2.68/t. The results showed that the initial investment in the prototype water hyacinth harvester was lower than for the two foreign models. The engine used in the V 4702 model was the biggest and so its fuel price was the highest. Furthermore, the maintenance and labor costs of the prototype were the lowest. There was little difference in the payback period among the three units. All three water hyacinth harvesters were considered a worthwhile investment based on net present value analysis. Finally, the main capital investment was associated with the initial purchase. In future, the prototype water hyacinth harvester will reduce the initial capital investment required compared to purchasing foreign brands.